1674 The KnifeSavers bleeding control campaign: an evaluation of the public education programme. Issue 12 (22nd November 2022) - Russell, Nicole; Tattam, Kristian; Callon, Josh; Jackson, Robert; Misra, Nikhil
Abstract : Aims, Objectives and Background: Penetrating trauma remains a leading cause of mortality in the United Kingdom with major haemorrhage a potentially preventable cause of death. KnifeSavers, a not-for-profit healthcare professional led organisation based at a regional major trauma centre, launched in 2019 to educate and empower the public how to manage a bleeding wound. There are three pillars of the campaign; an education programme, distribution of bleeding control packs and a public awareness campaign all focused on stopping major bleeding at scene. The aim of this review is to evaluate the response to the education programme and improvement in confidence and ability of the attendees to control major bleeding. Method and Design: Adult public members attending KnifeSavers education sessions between July 2021 and March 2022 were recruited to partake in pre and post event surveys. Utilising a 5-point Likert scale participants willingness and preparedness to manage bleeding knife related wounds were assessed. The data was comparatively measured, without accounting for attrition, to evaluate a change in response. Results and Conclusion: There were 137 responses to the pre survey and 74% retention rate for the post session survey (n=101). Despite a consistently high willingness in participants to intervene (93% pre session and 96% post), only 28% felt prepared to manage a bleeding wound prior to the education session, and 27% felt prepared to use a bleeding control kit. Following the session an increase to 98% of participants were prepared to deal with a bleeding wound, and 96% prepared use a bleeding control kit. Of note 97% of attendees stated it was important that training was delivered by health care professionals. This data suggests that the KnifeSavers education programme is an effective strategy in increasing public preparedness to manage life-threatening bleeding wounds and supports further expansion of the programme. A further mixed methods qualitative assessment including paired t-test statistical analysis is underway.